THE CONDITIONS OF SUCCESS OF CHINESE INVESTMENT MODEL - N. Korolyov; X. Han (Вестник университета)
The article deals with the specific features of the Chinese economy. The positive and negative effects of foreign investments on the country's economy have been analyzed. A list of organizational and economic conditions that lead to a successful investment policy is given. The analysis of such indicators as import, export, poverty, literacy, income stratification has been provided. It is concluded about the similarity of the economic situation of China and Russia and the possibility of using the accumulated experience to attract investment.